Morphological differentiation in giant salamanders, Andrias japonicus, A. davidianus, and their hybrids (Urodela, Cryptobranchidae), and its taxonomic implications - Hara, Sotaro; Nishikawa, Kanto; Matsui, Masafumi; Yoshimura, Masako (Zootaxa, 2023)
For a long time, it has been debated whether the two giant salamanders, Andrias japonicus from Japan and A. davidianus from China, are conspecific or heterospecific. Morphological information about their diagnostic characteristics has been limited, without considering sexual dimorphism and/or body size variation. Recently, A. davidianus, which was introduced into Japan sometime in the past, has been found to hybridize with A. japonicus in situ. Taxonomic identification of individuals involved in this unusual breeding is made based on mitochondrial and nuclear DNA analyses. This identification method is time-consuming and costly. Thus, developing easier methods of identification, such as utilizing external morphological characteristics, is urgently needed. In this study, we verify previous descriptions showing that A. davidianus has a longer relative tail length than A. japonicus, and the tubercles on the lower jaw and throat were present in both sexes of A. davidianus. In addition, many head characteristics were found to be relatively larger in A. davidianus than in A. japonicus, which were new distinguishing characters. These morphological differences help support the idea that these are heterospecific lineages. In hybrids, relative values of head width and tail length were larger than those of A. japonicus, and the tubercles on their lower jaw and throat were present as in A. davidianus, suggesting that the hybrids and A. davidianus are distinguishable from A. japonicus.